Exploring user experience and emotion during Open Distance Learning among university students - Nasruddin, Zan Asma; Aida Wati, Zainal Abidin; Nor Hapiza, Mohd Ariffin; Mohd Khairul Azmi, Hassan; Rahmah, Mokhtar (European Publisher, 2024)
During the COVID-19 pandemic, schools and universities in the affected countries were shut down to combat the spread of the virus. Institutes of higher learning have no choice but to use open distance learning (ODL) to stay in business. A pilot study to test the reliability of the survey instrument was conducted among 100 students from Universiti Teknologi MARA in order to assess the students' user experience and emotions towards ODL platform features. The instrument comprises two parts: a 27-item questionnaire measuring user experience and a 48-item questionnaire measuring user emotions. The user experience was evaluated based on four factors: the usefulness, desirability, accessibility, and usability of the ODL platform's features and functions. The instrument's alpha values for all 27 items measuring user experience and all 48 items measuring user emotions were 0.954 and 0.963, respectively. Consequently, the usability, desirability, and younger age of students contribute to the user experience. Usability has the highest correlation with user experience, while usefulness has the lowest correlation, albeit still significant.